Main mafic and accessory mineralogy in granites and greisens from selected occurrences in the A-type Graciosa Province, S-SE Brazil, and petrological implications - Siachoque Velandia, Astrid (2020)
A-type granites from the Graciosa Province in S-SE Brazil are broader grouped in two main petrographic associations: one alkaline including metaluminous and peralkaline alkali-feldspar granites and syenites, while the other aluminous is constituted by metaluminous to slightly peraluminous syeno- and monzo-granites. These granites are geochemically characterized by high iron and alkali contents and relative elevated abundances of LILEs, HFSEs, REEs and F. Moreover, they include a large variety of Fe- and HFSE-rich primary mafic silicate minerals as well as REE-rich magmatic and hydrothermal accessory minerals. This thesis studied main mafic silicates and accessory minerals in granites and greisens from the Mandira Granite Massif and the Desemborque and Papanduva Plutons in the province. Our results are grouped in four chapters and the main insights show that: 1) the Mandira Granite Massif contains magmatic calcic, sodic-calcic and sodic amphiboles and Al-rich annite as well as hydrothermal calcic and sodic amphiboles, annite, chlorite and stilpnomelane. The Mandira granites crystallized at 720- 750°C and 130-170 MPa (plagioclase-hornblende geothermobarometer) under relatively low to moderate fO2 conditions while during the late to post-magmatic evolution, the redox conditions indicate high oxidizing conditions and hydrothermal temperatures 250-272°C (chloritethermometry). 2) The Mandira and Papanduva peralkaline granites include late-magmatic and hydrothermal astrophyllite with relatively LILEs- and LREE-rich, the late-magmatic is more enriched in Zr-Nb than the hydrothermal which is more enriched in Ti. The last one was formed as result of the replacement of primary sodic amphiboles (in Mandira) and clinopyroxenes (in Papanduva). Accordingly, astrophyllite compositions offer additional information of redox conditions as well as magmatic and hydrothermal environments in peralkaline granitic systems. 3) In syenogranites and greisens from the Desemborque pluton we found the occurrence of columbite crystals characterized by predominant enrichment of HFSEs and HREEs which were formed from early to late post-magmatic stages. 4) Accessory minerals in the Desemborque rocks are magmatic zircon (syenogranites) and post-magmatic zircon, monazite, xenotime and fluorite (greisen), while in the Mandira granites are magmatic and post-magmatic zircon and fluorite and post-magmatic fluorides (fluocerite and gagarinite). In both occurrences, the postmagmatic phosphates and the fluorides were formed by several hydrothermal alterations of zircons due to post-magmatic fluids. In general, all zircons experienced post-magmatic alterations leading to progressive increase of HFSEs and REEs from primary to hydrothermal altered zircon. This hydrothermal activity was dating in monazite crystals from the Desemborque pluton given ages of 584 ± 3 Ma using the CHIME method. Highlighting, this thesis follows the magmatic, late magmatic and post-magmatic processes during the evolution of the Graciosa rocks which are registered in the mafic and accessory minerals studied here. In this sense the late to post-magmatic processes are associated with the circulation of hydrothermal HFSE- and F-rich fluids derived from the destabilization of magmatic minerals and subsequently promoted the significant enrichment of incompatible elements in the final evolutionary stages of the granitic systems.